In vitro effect of nesfatin-1 on contractions in the rat thoracic aorta - Barutcu, A.; Kacar, E.; Ercan, Z.; Kocaman, N.; Serhatlioglu, I; Kelestimur, H. (Wiley-Blackwell, 2015)
[Abstract Not Available]